2021
DOI: 10.3389/fmolb.2021.660456
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Profiles of Dietary and Microbial Metabolites in Formula- and Breastfed Infants

Abstract: The early-life metabolome of the intestinal tract is dynamically influenced by colonization of gut microbiota which in turn is affected by nutrition, i.e. breast milk or formula. A detailed examination of fecal metabolites was performed to investigate the effect of probiotics in formula compared to control formula and breast milk within the first months of life in healthy neonates. A broad metabolomics approach was conceptualized to describe fecal polar and semi-polar metabolites affected by feeding type withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 77 publications
3
21
0
Order By: Relevance
“…According to in vivo studies in weanling rats, higher concentrations of secondary bile acids (i.e., deoxycholic acid) were determined in the formula fed group. In line with our results, secondary bile acids may be representative metabolic products of probiotics, such as Bifidobacteria , or bacterial communities, such as Clostridia and Firmicutes , in FF infants from 1st to 3rd month of life [ 56 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to in vivo studies in weanling rats, higher concentrations of secondary bile acids (i.e., deoxycholic acid) were determined in the formula fed group. In line with our results, secondary bile acids may be representative metabolic products of probiotics, such as Bifidobacteria , or bacterial communities, such as Clostridia and Firmicutes , in FF infants from 1st to 3rd month of life [ 56 ].…”
Section: Discussionsupporting
confidence: 84%
“…In particular, primary and conjugated bile acids, key regulators in the formation of gut microecology by participating in bacterial metabolism, were detected in high amounts in healthy neonates [ 54 ]. Secretion of bile acids (mainly sulfated) is elicited by the presence of human milk lipids and is indirectly associated with increased presence of Veillonella , Bacteroides , Clostridium , Enterobacteriaceae and Streptococcus taxa in BF newborns [ 55 , 56 ]. According to in vivo studies in weanling rats, higher concentrations of secondary bile acids (i.e., deoxycholic acid) were determined in the formula fed group.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high specificity, sensitivity, and speed, mass spectrometry (MS) has been a cornerstone of glycation product analysis for several decades. Many methods have been developed for the analysis of glycation products. High-resolution MS techniques enable simultaneous detection and identification of both early and advanced glycation products even in complex mixtures. This makes high-resolution MS particularly suitable for non-targeted glycation studies . The highly accurate precursor mass and fragmentation behavior are powerful features for structure elucidation and diagnostic fragment identification. Challenges in non-targeted analysis including the lack of commercial standards and the diversity of structures can be tackled using isotope labeling. …”
Section: Introductionmentioning
confidence: 99%
“…Various sterol lipids, glycerophospholipids and fatty acids additionally account for metabolites discriminating between infants of various feeding modalities [ 25 26 27 35 ]. We observed palmitic acid, oleic acid, stearic acid and linoleic acid to be the predominant lipids comprising the infant stool fatty acid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that breastfeeding alters the metabolic profile until about one year of age, at which point it has been postulated that the predominance of a solid food diet is responsible for the convergence. The analysis of infant fecal metabolite profiles may suggest that the overall variability demonstrated by each individual infant may reflect the interplay between genetic backgrounds and external influences, including the composition of maternal breast milk, amount consumed, and living environment [ 12 35 ].…”
Section: Discussionmentioning
confidence: 99%